Fixed points of (α, ψ)‐contractions in Hausdorff partial metric spaces. (4th September 2018) - Nazam, Muhammad; Acar, Özlem
Abstract : The concept of ( α, ψ )‐contractions was introduced by Samet et al. in this paper, we introduce ( α, ψ )‐generalized contractions in a Hausdorff partial metric space. We discuss its significance and obtain some common fixed point theorems for a pair of self‐mappings. Some examples are given to support the theory.